X-ray scattering at beamline BL2 of DELTA: Studies of lysozyme-lysozyme interaction in heavy water and structure formation in 1-hexanol. Issue 1 (1st December 2022) - Dargasz, M; Bolle, J; Faulstich, A; Schneider, E; Kowalski, M; Sternemann, C; Savelkouls, J; Murphy, B; Paulus, M
Abstract: The experimental station of the bending magnet beamline BL2 of the Dortmund Synchrotron Radiation Source DELTA has been reconstructed in order to enable small-angle X-ray scattering and wide-angle scattering studies with monochromatic beam. By using a multilayer monochromator with a bandwidth of 1.5%, it is possible to reach a photon energy of 12 keV at sufficiently high photon fluxes. The beamline layout is described and the experimental capabilities are discussed by giving two examples of typical experiments: (i) A dense lysozyme solution is studied using small-angle X-ray scattering in order to reveal to influence of pressure on the protein-protein interaction with heavy water as solvent. (ii) The dependency of the hydrogen-bond mediated structure formation on temperature and pressure is investigated in liquid 1-hexanol by wide-angle X-ray scattering.